Life after the Pandemic: Economic and Social Consequences - V. I. Grishin; D. V. Domashchenko; L. V. Konstantinova; A. P. Koshkin; E. V. Ustyuzhanina; D. A. Shtykhno; E. V. Shubenkova (Вестник Российского экономического университета имени Г. В. Плеханова, 2020)
The article was written at the height of the coronavirus pandemic, when unprecedented restrictive measures were taken regarding the activities of a large proportion of economic actors to ensure a regime of self-isolation and social distance. The article attempts, on the basis of a synthesis of expert and analytical materials published during the pandemic in various information sources and the results of sociological studies assessing its real socio-economic consequences, to provide forecasts for the near and distant prospects, taking into account various parameters of an economic and social nature. The impact of the pandemic on macroeconomic indicators, the situation on the labor market, the dynamics of income of the population was considered. The social consequences of the pandemic are analysed separately, in particular in the field of health care, education, social support, social and labour relations, as well as the peculiarities of the relationship between power and society. The Russian economy is facing a recession corresponding to the long-term recession of the world economy. According to the authors, the scale and social consequences of this recession can be reduced for Russia. The formation of an anti-crisis fund to support economic sectors and citizens against the background of the coronavirus situation should lead at all levels of government to the adoption of constructive management decisions and the effective use of each ruble.